The Role of E-Trust and User Experience on Online Purchasing Decisions with Discounts as a Moderating Variable for Shopee Consumers of Erigo Fashion Products - Masitoh Masitoh; Irma Yunita; Muhamad Agung Dharmajaya (SEAN Institute, 2026)
This study aims to analyze the influence of user experience and e-trust on online purchasing decisions for Erigo fashion brand products on the Shopee platform in Pandeglang Regency, with discounts as a moderating variable. The study used an associative quantitative approach with the SEM-PLS method on 140 Shopee user respondents selected through random sampling techniques in five sub-districts in Pandeglang Regency. The results showed that user experience had no significant effect on online purchasing decisions, while e-trust had a positive and significant effect on purchasing decisions. In addition, the discount variable was unable to moderate the relationship between user experience and e-trust on purchasing decisions. The research findings confirm that digital trust is the main factor influencing consumer decisions in purchasing fashion products online compared to user experience or price promotion stimuli. This study contributes to the development of digital consumer behavior studies, especially in fashion marketplaces in developing regions, and serves as a strategic reference for e-commerce platforms in increasing consumer trust.